Chemopreventive effect of myrtenal on bacterial enzyme activity and the development of 1,2-dimethyl hydrazine-induced aberrant crypt foci in Wistar Rats - Booupathy, Lokesh Kumar; Venkatachalam, Sathishkumar; Natarajan, Nandakumar; Thamaraiselvan, Rengarajan; Arumugam, Madankumar; Periyasamy, Balasubramanian Maruthaiveeran (Elsevier, 2016)
Colon cancer remains as a serious health problem around the world despite advances in diagnosis and treatment. Dietary fibers are considered to reduce the risk of colon cancer as they are converted to short chain fatty acids by the presence of anaerobic bacteria in the intestine, but imbalanced diet and high fat consumption may promote tumor formation at different sites, including the large bowel via increased bacterial enzymes activity. The present study was conducted to characterize the inhibitory action of myrtenal on bacterial enzymes and aberrant crypt foci (ACF). Experimental colon carcinogenesis induced by 1,2- dimethylhydrazine is histologically, morphologically, and anatomically similar to human colonic epithelial neoplasm. Discrete microscopic mucosal lesions such as ACF and malignant tumors function as important biomarkers in the diagnosis of colon cancer. Methylene blue staining was carried out to visualize the impact of 1,2-dimethylhydrazine and myrtenal. Myrtenal-treated animals showed decreased levels of bacterial enzymes such as b-glucuronidase, b-glucosidase, and mucinase. Characteristic changes in the colon were noticed by inhibiting ACF formation in the colon.